Analisis Alternatif Prioritas Pemecahan Masalah Pencegahan dan Pengendalian Infeksi di Hospital Nacional Guido Valadares Dili Timor-Leste - Virgilio Soares; Chatarina Umbul Wahyuni (Universitas Airlangga, 2024)
Introduction: Infection prevention and control in hospitals is a practical approach based on real evidence to prevent patients, families and visitors as well as health workers from the risk of infection. Purpose: Purpose of this study was to determine alternative priorities for solving infection prevention and control problems at Hospital Nacional Guido Valadares Dili, Timor Leste. Methods: The method used in this research is qualitative research using interviews and focus group discussions involving 3 key informants consisting of the Executive Director, Clinical Director and Director of nursing and midwifery and 16 informants consisting 1 head of the Quality Control department, 13 head of rooms and 2 educators. Data analysis through several stages, namely problem identification, problem prioritization with the non-scoring Delphi, root cause of the problem with the Fishbone diagram and determining alternative priority problem-solving using the Capability, Accessibility, readiness and leverage (CARL) method. Results: The results of the analysis show that the prevention and control of infections that are not running optimally have obstacles from the Human Aspects, Methods, Budget, Material and Machine or tools, based on the results of the analysis of alternative problem-solving priorities using the CARL method from the first and second rank are Conducting training for surveillance personnel, monitoring and evaluating infection prevention and control activities regularly. Conclusion: Based on the analysis of alternative priority problem solving using the CARL Method is to organize training for surveillance personnel, conduct regular monitoring and evaluation of prevention activities. Monitoring and evaluation should be carried out regularly to monitor the implementation of intervention activities and evaluate infection prevention and control activities, surveillance activities so as to ensure targeted achievements.